Italian urbanism between reform and counter-reform (Ciudades, 2017)
Urban reform is expected in Italy since 1963, when a law for the reform of the urban regulation of 1942, which could have modified the quality of the following territorial transformations, was presented. Nevertheless, the Parliament didn’t pass it because it would reduce radically the relevance of estate rent for the economy. Until now several measures have been approved, some of them positives, but not a new law; even for the confrontation between reformists, who stand for a new model of structural-strategic plan able of adapting to the new territorial realities in develop, and conservatives, who are against the improvement of the model established in the law of 1942. Opposite, the institutional frame has completely changed since the year 2003. Since then, the law competencies on urbanism have been transferred to regional governments and a kind of “urban federalism”, provided of elements that lead to confusion, has been created. Nowadays a new national law for the constitutional review of the competencies of Estate-Regions is under discussion. This one returns to some of the main principles of urbanism, and also to a lot of solutions that have already been proved by several regional regulations. As these rules have been promoted by the Government, they will probably be approved, ending the long-term Italian urban reform.
Keywords: rent; urban reform; new model of urban planning